Does glucagon-like peptide-1 (GLP-1) receptor agonist stimulation reduce alcohol intake in patients with alcohol dependence: study protocol of a randomised, double-blinded, placebo-controlled clinical trial. Issue 7 (16th July 2018) - Antonsen, Kerstin K; Klausen, Mette K; Brunchmann, Amanda S; le Dous, Nina; Jensen, Mathias E; Miskowiak, Kamilla Woznica; Fisher, Patrick M; Thomsen, Gerda K; Rindom, Henrik; Fahmy, Thomas P; Vollstaedt-Klein, Sabine; Benveniste, Helene; et al.
Abstract : Introduction: Alcohol dependence is a major public health problem. It is underdiagnosed and undertreated. Even when treated, more than 2/3 of patients in abstinence-oriented treatment will relapse within the first year. Thus, there is an urgent need for efficacious medical treatment of alcohol dependence. Glucagon-like peptide-1 (GLP-1) receptor stimulation has proven to reduce alcohol consumption in preclinical experiments. However, the effect of GLP-1 receptor agonists in humans has to our knowledge, not yet been investigated. Methods and analysis: Design, participants and intervention : The effect of the once-weekly GLP-1-receptor-agonist exenatide will be investigated in a double-blinded, placebo-controlled, randomised clinical trial. 114 outpatients will be recruited and randomised to treatment with either placebo or exenatide once weekly for 26 weeks as a supplement to cognitive–behavioural therapy. The primary endpoint is reduction in number of 'heavy drinking days'. The secondary endpoints include changes in total alcohol consumption, days without consumption, changes in brain activity and function, smoking status, cognition, measures of quality of life and changes in phosphatidylethanol as a biomarker of alcohol consumption from baseline to follow-up at week 26. Status : Currently recruiting patients. Ethics and dissemination: Ethical approval has been obtained. Before screening, all patients will be provided oral and written information about the trial. The study results will be disseminated by peer-review publications and conference presentations and has the potential to reveal a completely new medical treatment of alcohol dependence.